THE IMPLEMENTATION OF ISLAMIC VALUES TO STUDENTS OF SD MUHAMMADIYAH 5 PALEMBANG DURING THE COVID-19 PANDEMIC - Nurbuana Nurbuana (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2021)
The purpose of this study was to find out the ways in instilling Islamic values to students at SD Muhammadiyah 5 Palembang in the course of pandemic. During the Covid-19 pandemic, all activities accentuate the use of technological advances and were carried out online. The research method used was a qualitative method. Data collection was taken by conducting interviews and observations. Interviews were conducted orally with the headmaster and several teachers including Al-Islam teachers, classroom teachers and teachers in the field of study involved in the implementation of Islamic activities for students at SD Muhammadiyah 5. Furthermore, observations were made to observe the religious activities performed by the students. As the results of the study, information was obtained that the instilling of Islamic values in SD Muhammadiyah 5 Palembang students during the covid-19 pandemic was executed online (remotely) and offline (face to face), scilicet by instilling habits in students to carry out religious activities such as dispersing greetings (salaam), recitation activities, and memorizing short surah that were established online. As for the implementation of congregational prayers and the Qur’an, it was fulfilled once a week while still adhering to health protocols.